Research on the planar‐coil linear time grating. Issue 13 (8th November 2018) - Zhang, Rui; Wu, Liang; Peng, Donglin; Liu, Yang; Peng, Lingli
Abstract : This article proposes a planar‐coil linear time grating displacement sensor. Compared with the existing magnetic field‐type linear time grating, the structure without tooth and slot improves the velocity uniformity of travelling wave magnetic field and the measurement accuracy can be greatly improved. The two‐phase excitation coils are arranged to form a plane coil array, and the travelling wave magnetic field is generated after the two‐phase orthogonal signals are entered, respectively. Then, the electric travelling wave signal is induced by the pickup coils, and the displacement is obtained after processing. The signal processing circuit is designed to amplify and filter the electric travelling wave signal, and the accuracy experiment is carried out. Result shows that in the range of 240 mm (full‐scale), the measurement accuracy can achieve ±0.8 μm.